THE EFFECT OF SHARIA SUPERVISORY BOARD CHARACTERISTICS ON FINANCIAL PERFORMANCE OF ISLAMIC BANKS IN INDONESIA - Hendri Mauliansyah (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
This study investigates the influence of Sharia Supervisory Board (SSB) characteristics on the financial performance of Islamic banks in Indonesia, where governance quality is vital amid rapid industry growth. Using a qualitative research design that integrates semi-structured interviews with SSB members and senior executives, direct observation of board meetings, and document analysis of annual financial reports, the study applies triangulation and thematic analysis to capture the impact of qualifications, independence, diversity, and professional experience on organizational outcomes. The findings demonstrate that SSB members with advanced educational and professional expertise significantly improve profitability indicators such as Return on Assets (ROA) and Return on Equity (ROE), while frequent and structured meetings enhance operational efficiency and ensure compliance with Sharia principles. Independence within the board strengthens accountability and reduces non-performing loans, whereas gender and professional diversity foster innovation, customer engagement, and market expansion. Furthermore, the alignment of SSB oversight with banks’ strategic planning amplifies financial sustainability and growth. The study reframes the role of SSB from compliance to strategic governance, consistent with corporate governance perspectives. Practically, it highlights the need for banks to recruit qualified and diverse SSB members, institutionalize continuous training, and integrate them into strategic decision-making, while regulators should encourage diversity and establish qualification standards. Future research should adopt longitudinal and cross-country approaches to deepen understanding of how SSB dynamics shape performance in different contexts.